Bioethanol Production From Hydrolyzed Lignocellulosic After Detoxification Via Adsorption With Activated Carbon and Dried Air Stripping - Artifon, Wagner; Bonatto, Charline; Bordin, Eduarda R.; Bazoti, Suzana F.; Dervanoski, Adriana; Alves, Sérgio L.; Treichel, Helen (Frontiers in Bioengineering and Biotechnology, 2018)
Bioethanol production has been presented as an alternative for supplying energy demand and minimizing greenhouse gases effects. However, due to abrasively conditions employed on the biomass during pretreatment and hydrolysis processes, inhibitors for fermentation phase such as acetic acid and others can be generated. Based on this problem, the aim of this work was to evaluate the adsorption of acetic acid on microporous activated carbon and investigate the stripping of the same component with dried air. For adsorption process, three concentrations of acetic acid (5, 10, and 20%) were analyzed by adsorption kinetics and adsorption isotherms (Langmuir and Freundlich models). Pseudo-second order model showed to fit better when compared to Pseudo-first order model. The Intraparticle Diffusion model presented the first phase of the adsorption as the regulating step of the adsorption process. The Langmuir model showed the best fitting, and the maximum capacity of adsorption was found as 128.66 mg.g−1. For stripping procedure an apparatus was set in order to insert dried air by a diffusor within the solution in study. Increasing temperature showed to be determinant on augmenting acetic acid evaporation in 2.14 and 6.22 times for 40 and 60°C when comparing it to 20°C. The application of the pickling process for removal of fermentation inhibitors in sugarcane bagasse hydrolyzed allowed the production 8.3 g.L−1 of ethanol.